Articular inflammation is controlled by myeloid cell-derived interleukin 1 receptor antagonist during the acute phase of arthritis in mice. Issue 2 (9th November 2011) - Lamacchia, Céline; Rodriguez, Emiliana; Palmer, Gaby; Vigne, Solenne; Martin, Praxedis; Talabot-Ayer, Dominique; Seemayer, Christian A; Gabay, Cem
Abstract : Objectives: To define the cell type (myeloid vs other cells) specific effect of interleukin 1 (IL-1) receptor antagonist (IL-1Ra) deficiency on the acute inflammatory phase of arthritis. Methods: Arthritis was induced by K/BxN serum transfer in wild-type (WT), IL-1Ra-deficient (IL-1Ra −/− ) and conditional knockout mice. In the latter, IL-1Ra production was specifically targeted in myeloid cells (IL-1Ra ΔM ) or in both hepatocytes and myeloid cells (IL-1Ra ΔH+M ). Arthritis severity was clinically evaluated and ankle sections were scored for synovial inflammation and cartilage erosion. Quantitative RT-PCR, western blot and immunohistochemical analyses measured expression, localisation and cellular sources of the different IL-1Ra isoforms in arthritic joints. Results: Total and myeloid cell-specific IL-1Ra deficiency was associated with increased arthritis severity, although disease incidence was similar to that of WT mice. Increased clinical scores were associated with exacerbated synovial inflammation. All IL-1Ra isoforms, except for intracellular (ic)IL-1Ra2, were expressed in arthritic joints of WT mice. In contrast, production of secreted (s)IL-1Ra and icIL-1Ra3 isoforms was markedly decreased in arthritic joints of both IL-1Ra ΔM and IL-1Ra ΔH+M mice. Immunohistochemical and western blot analyses suggested that the icIL-1Ra1 isoform is produced primarily by synovial fibroblasts. Conclusion: Myeloid cell-derived IL-1Ra, including both sIL-1Ra and icIL-1Ra3 isoforms, controls articular inflammation during the acute phase of K/BxN serum transfer-induced arthritis.